1997
DOI: 10.1016/s0376-8716(97)00038-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in network characteristics and HIV risk behavior among injection drug users

Abstract: Studies indicate that HIV risk behaviors vary greatly among injection drug users (IDUs). The source of such variation is often ascribed to individual differences, but much of it is due to how IDUs are grouped into social networks. Nevertheless, given the turbulent and uncertain lives led by many IDUs, it would not be surprising if their social networks changed substantially over time. We used data from a study of the social networks of IDUs in Chicago and Washington, DC, to examine changes in individual behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 35 publications
2
44
1
Order By: Relevance
“…107,108 Studies in various US cities have identified large social networks of injection drug users. [109][110][111][112][113][114][115][116][117][118] A key conclusion of these studies is that prevention efforts are more effective when they are targeted to individuals who are centrally located in high-risk networks than when they reach individuals on the periphery of such networks. If incremental methadone capacity were targeted to injection drug users who are centrally located in networks, then such expansion would likely be more costeffective than we have estimated; and if incremental capacity reached injection drug users located on the periphery of networks, then such expansion would likely be less cost-effective than we have estimated.…”
Section: Discussionmentioning
confidence: 99%
“…107,108 Studies in various US cities have identified large social networks of injection drug users. [109][110][111][112][113][114][115][116][117][118] A key conclusion of these studies is that prevention efforts are more effective when they are targeted to individuals who are centrally located in high-risk networks than when they reach individuals on the periphery of such networks. If incremental methadone capacity were targeted to injection drug users who are centrally located in networks, then such expansion would likely be more costeffective than we have estimated; and if incremental capacity reached injection drug users located on the periphery of networks, then such expansion would likely be less cost-effective than we have estimated.…”
Section: Discussionmentioning
confidence: 99%
“…Since injection drug use is rather collective in nature and shaped by various environmental and structural factors, the likelihood of engaging in specific behaviors is often influenced by the broader 'risk environment' that surrounds the individual (Atlani et al 2000;Hoffmann et al 1997;Organista et al 2004;Rhodes 2002;Rhodes et al 2005;Soskolne and Shtarkshall 2002). While movers in our cohort are slightly younger than non-movers as we have previously described (Rachlis et al 2008), recent research has demonstrated that, in fact, younger populations of IDU are often relatively mobile (Hahn et al 2001(Hahn et al , 2008Lankenau et al 2008).…”
Section: Discussionmentioning
confidence: 46%
“…To formally test for differences over time and between movers and non-movers, we performed linear growth curve analyses. This method has been successfully used in IDU in the past, and models changes over time incorporating interaction terms to determine if changes over time differ significantly between groups (Hoffmann et al 1997;Vlahov et al 2001). By using generalized linear models with repeated measurements, models were constructed for each selected behavior with group (mover vs. non-mover) and period (before vs. after) as the explanatory variables.…”
Section: Analysesmentioning
confidence: 99%
“…2 One possible explanation is that geographic areas with higher population densities and higher contact rates, such as metropolitan areas in the Northeast, may have larger social networks, thereby increasing the likelihood of risky contact with an HIV-infected person. 16,17 We also compared HIV prevalence among persons receiving voluntary confidential HIV counseling and testing with the results of anonymous, unlinked HIV serosurveys conducted in the same drug treatment programs. In New York City and Newark, HIV prevalence in unlinked serosurveys of all entrants was at least three-fold higher than among persons who volunteered to undergo HIV counseling and testing.…”
Section: Discussionmentioning
confidence: 99%